DAYLIGHT ANALYSIS IN A ROOM WITH A KINETIC FAÃ§ADE FABRIC TENSILE STRUCTURE WITH RESPECT TO SKY DIFFUSE IRRADIANCE CHANGES - Rakannabyan Sugihartadi, Re
Daylight is an important aspect of sustainable building planning which is currently receiving a lot of attention. There are many approaches to take advantage of daylight with building façades, such as the use of fabric material for kinetic façades. One example of such façades is a prototype of kinetic tensile fabric structure façade (KBKT façade) designed by the ITB School of Architecture, Planning and Policy Development (SAPPK) and Bandung Manufacturing Polytechnic (POLMAN). For its application, KBKT façade is analyzed using diffuse horizontal irradiance (DHI) scenarios as the control system input and room depth scenarios to determine the relevant room depth for the use of the façade. KBKT facade prototype was examined on a 1 m x 1 m x 1 m room prototype. The façade prototype measures 0.8 x 0.8 m2 and has a screw rod movement variation of 0 – 10 cm with a step size of 1 cm. Daylight simulation was carried out using the Rhinoceros and Grasshopper software. Daylight analysis was carried out on scenarios of room depth of 2.8, 4.2 and 5.6 m with the geometry of the façade congruent and three times larger than prototype and DHI scenarios divided by the quartile method, namely 1 – 74 Wh/m2 (DHI 1), 74 – 133 Wh/m2 (DHI 2), 133 – 184 Wh/m2 (DHI 3), and 184 – 434 Wh/m2 (DHI 4). sDA300/50% metric that meets LEED v4.1 standards and the highest possible avUDI300-750 used as the optimal performance solution. Experiments were conducted to validate illuminance in the simulated room using DF metric. Results of the analysis show that the use of this facade at a room depth of 2.8 and 5.4 m are not provide a different optimal screw solutions in each DHI scenarios. Meanwhile, the room depth of 4.2 m has various optimal screw solutions, namely: variation 9 for DHI 1 scenario, variation 6 for DHI 2 scenario, variation 5 for DHI 3 scenario, and variation 2 for DHI 4 scenario .